Hydroxylamine intermediate governs selectivity in nitrite hydrogenation on Pd-based catalysts for sustainable water treatment - Janek Betting; Yardthip Preedawichitkun; Tawan Sooknoi; Leon Lefferts; Jimmy A. Faria Albanese (Journal of Materials Chemistry A, 2026)
Catalytic hydrogenation of nitrate (NO 3 − ) and nitrite (NO 2 − ) is a promising route for drinking water purification and rebalancing the global nitrogen cycle.
Keywords: Ammonia Synthesis and Nitrogen Reduction; Nanomaterials for catalytic reactions; Environmental remediation with nanomaterials